Sharh-i ta'sis va tarikhchah-'i vaqayi'-i Sazman-i Mujahidin-i Khalq-i Iran : (Intisharat-i Sazman-i Mujahidin-i Khalq-i Iran, 1979)
'Explanation about the establishment and the history of events of Mujahidin Khalq Iran'